2012
DOI: 10.1007/s00586-011-2142-6
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence and severity of musculoskeletal disorders in Swedish military personnel during peacekeeping operations in Afghanistan

Abstract: Musculoskeletal pain was common during peacekeeping mission and gradual onset was dominating. Most often, it did not affect the daily activities. Nevertheless, it may be of important to consider broadening the medical disciplines onsite to provide preventive measures and treatment at an early stage, and thereby reducing the risk of chronicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 15 publications
2
12
3
1
Order By: Relevance
“…Military soldiers often develop musculoskeletal health conditions ( Glad et al, 2012 ; Knapik et al, 2007 ) and depending on their severity they can lead to premature discharge ( Taanila et al, 2010 ). Several studies have demonstrated that soldiers often develop low back pain ( Taanila et al, 2010 ; Taanila et al, 2009 ; Jennings et al, 2008 ), particularly as they age ( Mattila et al, 2009 ; Hellsing and Bryngelsson, 2000 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Military soldiers often develop musculoskeletal health conditions ( Glad et al, 2012 ; Knapik et al, 2007 ) and depending on their severity they can lead to premature discharge ( Taanila et al, 2010 ). Several studies have demonstrated that soldiers often develop low back pain ( Taanila et al, 2010 ; Taanila et al, 2009 ; Jennings et al, 2008 ), particularly as they age ( Mattila et al, 2009 ; Hellsing and Bryngelsson, 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…Musculoskeletal injuries are common in the military ( Glad et al, 2012 ; Knapik et al, 2007 ; Kaufman et al, 2000 ; Knapik et al, 2004 ; Daube 1969 ; Bessen et al, 1987 ; Mäkelä et al, 2006 ). The primary reason for medical evacuation of US military personnel in Iraq and Afghanistan was musculoskeletal injuries ( Cohen et al, 2010 ), and musculoskeletal injuries remain a common reason for active duty military to utilize healthcare services ( Waitzkin and Noble, 2009 ; Mattila et al, 2006 ; Jones and Knapik, 1999 ).…”
Section: Introductionmentioning
confidence: 99%
“…Musculoskeletal pathology is one of the most common work-related health problems [1][2][3], as well as an important cause of morbidity for both civil population and military personnel [5][6][7]. It is an inflammatory and degenerative ailment that affects all individuals at working age.…”
Section: Introductionmentioning
confidence: 99%
“…The pain symptoms could be the initial symptom of musculoskeletal pathology which is an important cause of morbidity in the military service [5,6,9]. Finnish [11,12] Norwegian, Swedish [2], Danish Defence Force [5,6], the US Army [1,3] epidemiological studies have shown that pain symptoms are important for physically active conscripts, a significant number of training days is lost due to musculoskeletal disorders. The most important pain areas are those of lumbar spine (cervical and lumbar portion), and lower extremities.…”
Section: Introductionmentioning
confidence: 99%